Impact of Economic Crisis on Farmer Household and the Anticipation in Copnight - Mewa Ariani; Handewi P.S. Rachman; Sri Hastuti; . Wahida (Media Gizi dan Keluarga, 2001)
The aim of this study is to analyze the impact of economiccrisis on agricultural household and the act to anticipate its alleviation. This research was conducted in East Java province that has potential food crop and horticultural product and in Bali province which is potential in estate crops and handicrafts, with 60 household samples in each province. The results of this research are: (1) Food crop household is income is the smallest in term of absolut value; (2) horticultural house hold get the most severe impact of the economic crisis, in contrast, estate crop household getsthe positive impact from the economic crisis, and (3) the effort to aleviate the crisis is with drawing and using the saving, borrowing to formal/informal credit institutions, managing household consumption pattern.